Nursery rhyme comics : [50 timeless rhymes from 50 celebrated cartoonists] - Duffy, Chris (Comic book writer); McDonnell, Patrick, 1956- (First Second, 2011)
Presents fifty traditional nursery rhymes in comic book format, with illustrations by well-known cartoonists.